Composite silicon material and preparation method thereof, negative pole piece, secondary battery and electric device
By using composite silicon materials in secondary batteries, combined with porous conductive materials and ion-conducting materials, the problems of high expansion and poor kinetic performance of silicon-based negative electrode materials are solved, and higher energy density and better cycling performance are achieved.
Patent Information
- Application Number
- CN202311146150.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-09-06
AI Technical Summary
Silicon-based anode materials have problems of high expansion and poor kinetic performance in secondary batteries, which limits the further development of battery technology.
A composite silicon material is used, including a core and a silicon-containing cladding layer. The core is composed of a porous conductive material and a first silicon-based material. The outer surface of the porous conductive material has holes, and the first silicon-based material is embedded in the hole; the silicon-containing cladding layer is composed of an ion-conducting material and a second silicon-based material. The ion-conducting material increases the ion transmission path and improves the kinetic performance.
It effectively alleviates the silicon expansion problem, improves the dynamic performance of the secondary battery, improves the fast charging capability and cycling performance.
Smart Images

Figure CN119581505A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a composite silicon material and a preparation method thereof, a negative electrode sheet, a secondary battery and an electrical device. Background Art
[0002] Secondary batteries are widely used in various consumer electronic products and electric vehicles due to their outstanding features such as light weight, no pollution, and no memory effect. With the continuous development of the new energy industry, people have put forward higher and higher requirements on the energy density of secondary batteries.
[0003] Silicon-based negative electrode materials are widely used in secondary batteries due to their high capacity. However, due to the high expansion characteristics of silicon and its poor conductivity, while silicon-based negative electrode materials improve the energy density of secondary batteries, they also cause expansion and poor kinetics in secondary batteries, limiting the further development of battery technology. Summary of the invention
[0004] Based on this, it is necessary to provide a composite silicon material and a preparation method thereof, a negative electrode plate, a secondary battery and an electrical device to alleviate the expansion of the secondary battery and improve the dynamic performance of the secondary battery.
[0005] In order to achieve the above-mentioned object, the first aspect of the present application provides a composite silicon material, comprising:
[0006] A core, the core comprising a silicon-carbon material, the silicon-carbon material comprising a porous conductive material and a first silicon-based material, the porous conductive material having holes on its outer surface, at least a portion of the first silicon-based material being distributed in the holes; and
[0007] The silicon-containing coating layer is coated on the outer side of the inner core, and the silicon-containing coating layer comprises an ion-conducting material and a second silicon-based material, wherein the second silicon-based material is dispersed in the ion-conducting material.
[0008] The composite silicon material of the present application includes a silicon-carbon material and a silicon-containing coating layer. The silicon-carbon material includes a porous conductive material with holes on the outer surface and a first silicon-based material. At least a portion of the first silicon-based material is embedded in the holes of the porous conductive material, which can effectively alleviate the problem of silicon expansion. At the same time, the silicon-containing coating layer contains an ion-conducting material, which can increase the ion transmission path, thereby effectively alleviating the problem of poor kinetic performance caused by the small number of ion transmission paths of the silicon-carbon material.
[0009] In some embodiments, the silicon-containing coating has at least one of the following characteristics:
[0010] (1) The thickness of the silicon-containing coating layer is 5 nm-100 nm, and can be optionally 30 nm-60 nm;
[0011] (2) The ion-conducting material includes one or more of hard carbon, soft carbon, graphite, transition metal nitride, silicon-based alloy, tin-based alloy and lithium metal;
[0012] (3) The ion-conducting material and the second silicon-based material are composited into silicon oxide;
[0013] Optionally, the molar ratio of oxygen element to silicon element contained in the silicon oxide is denoted as x, 0<x<2, and may be 0<x≤0.6;
[0014] (4) The volume average particle size Dv50 of the second silicon-based material is 2nm-20nm, and can be 2nm-9nm;
[0015] (5) The second silicon-based material includes one or more of elemental silicon and silicon-tin alloy;
[0016] (6) The shape of the second silicon-based material includes one or more of particles, lines, spheres, quasi-spheres and flakes.
[0017] In some embodiments, the silicon-carbon material has at least one of the following characteristics:
[0018] (1) The mass proportion of silicon in the silicon-carbon material is 3%-25%, and can be 8%-10%;
[0019] (2) The pore diameter is 2nm-50nm, and can be 15nm-35nm;
[0020] (3) The stacking height of the first silicon-based material in the hole is 1 nm-35 nm, and can be 15 nm-25 nm;
[0021] (4) The shape of the silicon-carbon material includes one or more of granular, spherical and quasi-spherical shapes;
[0022] (5) The first silicon-based material includes one or more of elemental silicon and silicon-tin alloy;
[0023] (6) The shape of the first silicon-based material includes one or more of particles, lines, spheres, quasi-spheres and flakes;
[0024] (7) The porous conductive material includes porous carbon.
[0025] In some embodiments, at least 3% of the first silicon-based material is embedded in the pores;
[0026] Optionally, all of the first silicon-based materials are embedded in the holes.
[0027] In some embodiments, the composite silicon material further includes a first carbon coating layer, wherein the first carbon coating layer is located between the substrate and the silicon-containing coating layer;
[0028] Optionally, the first carbon coating layer has at least one of the following characteristics:
[0029] (1) The thickness of the first carbon coating layer is 10 nm to 30 nm;
[0030] (2) The material of the first carbon coating layer includes amorphous carbon.
[0031] In some embodiments, the composite silicon material further includes a second carbon coating layer, wherein the second carbon coating layer is coated on the outside of the silicon-containing coating layer;
[0032] Optionally, the second carbon coating layer has at least one of the following characteristics:
[0033] (1) The thickness of the second carbon coating layer is 10 nm to 30 nm;
[0034] (2) The material of the second carbon coating layer includes amorphous carbon.
[0035] In some embodiments, the composite silicon material has a shape including one or more of granular, spherical, and quasi-spherical;
[0036] Optionally, the volume average particle size Dv50 of the composite silicon material is 3 μm-22 μm, and optionally 5 μm-10 μm.
[0037] The second aspect of the present application provides a method for preparing the composite silicon material of the first aspect of the present application, comprising the following steps:
[0038] preparing the silicon-carbon material;
[0039] The silicon-containing coating layer is formed on the outer side of the silicon-carbon material.
[0040] The third aspect of the present application provides a method for preparing the composite silicon material of the first aspect of the present application, comprising the following steps:
[0041] preparing the silicon-carbon material;
[0042] Forming a silicon dioxide coating layer on the outer side of the silicon-carbon material to prepare an intermediate with a silicon dioxide coating layer;
[0043] The intermediate is reduced to form the silicon-containing coating layer on the outer side of the silicon-carbon material.
[0044] In some embodiments, the silicon-carbon material is prepared by vapor deposition;
[0045] Optionally, the vapor deposition method includes at least one of the following conditions:
[0046] (1) The raw materials for preparing the silicon-carbon material include a porous conductive material and a first silicon source;
[0047] Optionally, the molar ratio of the porous conductive material to the first silicon source is (3-8):1;
[0048] Optionally, the first silicon source includes monosilane;
[0049] Optionally, the porous conductive material comprises porous carbon;
[0050] (2) The reaction temperature of the vapor deposition method is 800°C-900°C, and the reaction time is 2h-8h;
[0051] (3) The reaction atmosphere of the vapor deposition method includes an inert gas.
[0052] In some embodiments, a silicon dioxide coating layer is formed on the outside of the silicon-carbon material by a hydrothermal method;
[0053] Optionally, the hydrothermal method includes at least one of the following conditions:
[0054] (1) The raw materials for preparing the silicon dioxide coating layer include a second silicon source;
[0055] Optionally, the second silicon source includes tetraethyl orthosilicate;
[0056] Optionally, the mass ratio of the silicon-carbon material to the second silicon source is 3:(1-5);
[0057] (2) The reaction temperature of the hydrothermal method is 110°C-130°C, and the reaction time is 0.5h-5h;
[0058] (3) The reaction medium of the hydrothermal method comprises a mixture of ethanol and water;
[0059] Optionally, the volume ratio of ethanol to water in the mixed solution is (2-4):1.
[0060] In some embodiments, the intermediate is reduced by magnesium thermal reduction;
[0061] Optionally, the magnesium thermal reduction method includes at least one of the following conditions:
[0062] (1) The reducing agent used includes magnesium powder;
[0063] Optionally, the mass ratio of the intermediate to the magnesium powder is (2-4):1;
[0064] (2) The reaction temperature of the magnesium thermal reduction method is 600°C-750°C, and the reaction time is 0.5h-10h.
[0065] In some embodiments, before the step of forming a silicon dioxide coating layer on the outer side of the silicon-carbon material, the method further comprises:
[0066] Using a first carbon source to prepare a first carbon coating layer on the outer side of the silicon-carbon material;
[0067] Optionally, preparing the first carbon coating layer includes at least one of the following conditions:
[0068] (1) The first carbon source includes acetylene;
[0069] (2) adding a first dilution gas when preparing the first carbon coating layer, wherein the first dilution gas includes an inert gas;
[0070] Optionally, the first dilution gas includes argon;
[0071] Optionally, the volume ratio of the first carbon source to the first dilution gas is (0.5-2):9;
[0072] (3) The reaction temperature is 600°C-800°C, and the reaction time is 0.5h-2h.
[0073] In some embodiments, the preparation method further comprises:
[0074] Using a second carbon source to form a second carbon coating layer on the outer side of the silicon-containing coating layer;
[0075] Optionally, preparing the second carbon coating layer includes at least one of the following conditions:
[0076] (1) The second carbon source includes acetylene;
[0077] (2) adding a second dilution gas when preparing the second carbon coating layer, wherein the second dilution gas includes an inert gas;
[0078] Optionally, the second dilution gas includes argon;
[0079] Optionally, the volume ratio of the second carbon source to the second dilution gas is (0.5-2):9;
[0080] (3) The reaction temperature is 600°C-800°C, and the reaction time is 0.5h-2h.
[0081] A fourth aspect of the present application provides a negative electrode sheet, comprising:
[0082] A negative electrode current collector; and
[0083] The negative electrode active material layer is located on at least one side of the negative electrode current collector, and the negative electrode active material layer includes the composite silicon material of the first aspect of the present application or the composite silicon material prepared by the method of the second aspect of the present application.
[0084] The fifth aspect of the present application provides a secondary battery, comprising the negative electrode plate of the third aspect of the present application.
[0085] The sixth aspect of the present application provides an electrical device, comprising the secondary battery of the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0086] Figure 1 is a schematic diagram of a secondary battery according to one embodiment of the present application.
[0087] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.
[0088] Figure 3 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0089] Figure 4 is a SEM image of the cross section of the composite silicon material in Example 1.
[0090] Description of reference numerals:
[0091] 1 secondary battery; 11 housing; 12 electrode assembly; 13 cover plate; 2 power-consuming device. DETAILED DESCRIPTION
[0092] In order to facilitate the understanding of the present application, the present application will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present application are given in the drawings. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0093] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0094] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0095] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0096] In this application, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left endpoint and the right endpoint are the same. For example, 10-1000nm means that the units of the left endpoint "10" and the right endpoint "1000" are both nm (nanometers).
[0097] In this application, "multiple", "multiple", "multiple times" and the like, unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "multiple" means greater than or equal to two. Only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and similarly any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, each separately disclosed point or single value itself can be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unambiguous range.
[0098] The "range" disclosed in this application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values.
[0099] The temperature parameters in this application, unless otherwise specified, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range of instrument control.
[0100] If there is no special description, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. If there is no special description, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.
[0101] If there is no special explanation, all the steps of the present application can be performed sequentially or randomly, preferably sequentially.
[0102] Silicon-based negative electrode materials are widely used in secondary batteries. However, due to the high expansion characteristics of silicon, its few ion transmission paths and poor conductivity, secondary batteries using silicon-based negative electrode materials in related technologies have problems of poor expansion and kinetic performance while improving energy density.
[0103] Based on the above problems, the present application combines a silicon-containing coating layer comprising an ion-conducting material and a silicon-carbon material. The silicon-carbon material includes a porous conductive material having holes on the outer surface and a first silicon-based material, and at least a portion of the first silicon-based material is embedded in the holes. The holes can provide space for the expansion of the first silicon-based material, thereby alleviating the problem of an increase in the overall volume of the composite silicon material due to the expansion of the first silicon-based material; and the ion-conducting material in the silicon-containing coating layer located on the outside of the silicon-carbon material can increase the ion transmission path, thereby improving the kinetic properties of the composite silicon material.
[0104] The first aspect of the present application provides a composite silicon material, including an inner core and a silicon-containing coating layer coated on the outside of the inner core; the inner core contains a silicon-carbon material, the silicon-carbon material includes a porous conductive material and a first silicon-based material, the outer surface of the porous conductive material has holes, and at least part of the first silicon-based material is distributed in the holes; the silicon-containing coating layer contains an ion-conducting material and a second silicon-based material, and the second silicon-based material is dispersed in the ion-conducting material.
[0105] It should be noted that the "first silicon-based material" in this application is only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can it be understood as implicitly indicating the importance or quantity of the indicated technical features.
[0106] A porous conductive material refers to a conductive material having holes on its outer surface and / or inside, and the number of holes contained in the porous conductive material may be one or more. The first silicon-based material in the silicon-carbon material may be distributed entirely in the holes of the porous conductive material, or only a portion of the first silicon-based material may be distributed in the holes of the porous conductive material.
[0107] The ion-conducting material may include a material that has ion-conducting ability itself, or may include a material that can form a compound with ion-conducting properties after further reaction; for example, the ion-conducting material may include a material that can form a compound with ion-conducting properties during the battery charging process, etc., and is not specifically limited. The silicon-containing coating layer may be a continuous and complete coating layer, or it may be an incomplete coating layer; wherein, "complete" means that the substance located on the inner side of the silicon-containing coating layer is completely coated by the silicon-containing coating layer, and the silicon-containing coating layer completely isolates the substance inside it from the outside. "Incomplete" means that the substance located on the inner side of the silicon-containing coating layer is not completely coated by the silicon-containing coating layer, and the substance inside the silicon-containing coating layer can at least partially contact the outside of the silicon-containing coating layer. Preferably, the silicon-containing coating layer is a continuous and complete coating layer.
[0108] Understandably, the composite silicon material of the present application includes silicon-carbon material and ion-conducting material, wherein the silicon-carbon material includes a porous conductive material with holes on the outer surface and a first silicon-based material, and at least part of the first silicon-based material is embedded in the holes of the porous conductive material, which can effectively alleviate the problem of silicon expansion; at the same time, the ion-conducting material can increase the ion transmission path, thereby effectively alleviating the problem of poor dynamic performance caused by the small number of ion transmission paths of the silicon-carbon material. In addition, the fast charging capability and cycle performance of the secondary battery can also be improved.
[0109] In some embodiments, the thickness of the silicon-containing coating layer is 5nm-100nm. When the thickness of the silicon-containing coating layer is lower than the above range, the increase in the ion transmission path is limited, and the dynamic performance of the composite silicon material is poor; when the thickness of the silicon-containing coating layer is higher than the above range, the silicon content of the composite silicon material as a whole is too high, so that the composite silicon material expands too much, which may cause the SEI film on the surface of the composite silicon material to rupture, expose new sites, and the electrolyte continues to repair the SEI film at the damaged interface, consuming active lithium and affecting the battery cell cycle performance; at the same time, the expansion of the composite silicon material will deteriorate the energy density of the battery cell. As an example, the thickness of the silicon-containing coating layer can be, but is not limited to, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm or a range between any two of the above values. Optionally, the thickness of the silicon-containing coating layer is 30nm-60nm.
[0110] As an example, the thickness of the above-mentioned silicon-containing coating layer can be measured by transmission electron microscopy (TEM).
[0111] In some embodiments, the ion-conducting material includes one or more of hard carbon, soft carbon, graphite, transition metal nitrides, silicon-based alloys, tin-based alloys, and lithium metal.
[0112] In some embodiments, the ion-conducting material and the second silicon-based material are compounded into silicon oxide; silicon oxide refers to a compound containing both silicon and oxygen elements; when the ion-conducting material and the second silicon-based material can be compounded into silicon oxide, the ion-conducting material is silicon dioxide, and the second silicon-based material is dispersed in the ion-conducting material; during the charging process, silicon dioxide can undergo an electrochemical reaction with lithium released from the positive electrode active material to form lithium silicate having ion conductive properties.
[0113] In some optional embodiments, the molar ratio of oxygen to silicon contained in silicon oxide is recorded as x, 0<x<2. When the molar ratio of oxygen to silicon contained in silicon oxide is within the above range, the larger the value of x, the smaller the volume expansion of silicon oxide, but its gram capacity is also lower; the smaller the value of x, the higher the gram capacity of silicon oxide, but its volume expansion is also larger. As an example, the molar ratio of oxygen to silicon contained in silicon oxide can be but not limited to 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 1.95, 1.99 or the range between any two of the above values. Optionally, 0<x≤0.6. As an example, the molar ratio of oxygen and silicon in the silicon oxide mentioned above can be determined by the following method: perform X-ray energy dispersive spectroscopy (EDS) on the composite silicon material, deduct the silicon content in the silicon-carbon material, and qualitatively determine the x value in the silicon oxide.
[0114] It should be noted that the "second silicon-based material" in this application is used for descriptive purposes only and cannot be understood as indicating or implying relative importance or quantity, nor can it be understood as implicitly indicating the importance or quantity of the indicated technical features.
[0115] In some optional embodiments, the volume average particle size Dv50 of the second silicon-based material is 2nm-20nm; when the volume average particle size Dv50 of the second silicon-based material is within the above range, the strain caused by different lithium concentrations is smaller, and it can withstand greater strain without breaking; in addition, the active specific surface area of the second silicon-based material is larger and has relatively good dynamics. As an example, the volume average particle size Dv50 of the second silicon-based material can be, but is not limited to, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, 20nm or a range between any two of the above values. Optionally, the volume average particle size Dv50 of the second silicon-based material is 2nm-9nm.
[0116] As an example, the volume average particle size Dv50 of the second silicon-based material mentioned above can be measured with reference to GB / T 19077-2016 particle size distribution laser diffraction method, using a laser particle size analyzer, for example, Mastersizer 2000E laser particle size analyzer from Malvern Instruments Ltd., UK.
[0117] In some embodiments, the second silicon-based material includes one or more of elemental silicon and a silicon-tin alloy.
[0118] In some embodiments, the second silicon-based material has a shape including one or more of a particle, a wire, a sphere, a spheroid, and a flake.
[0119] In some embodiments, the mass proportion of silicon in the silicon-carbon material is 3%-25%; when the mass proportion of silicon in the silicon-carbon material is within the above range, the silicon-carbon material has a higher gram capacity and its electrochemical performance is relatively stable, and the cycle life is better; when the content of silicon increases further, the conductivity of the silicon-carbon material particles drops sharply, resulting in capacity decay. As an example, the mass proportion of silicon in the silicon-carbon material can be but is not limited to 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25% or a range between any two of the above values. Optionally, the mass proportion of silicon in the silicon-carbon material is 8%-10%.
[0120] As an example, the mass percentage of silicon element in the silicon-carbon material can be qualitatively determined using EDS energy spectrum.
[0121] In some embodiments, the pores of the porous conductive material have a pore size of 2nm-50nm; when the pore size of the porous conductive material is within the above range, while providing expansion space, the deterioration of the compaction density caused by the porous conductive material having internal reserved holes can be minimized, thereby improving the energy density. As an example, the pore size of the porous conductive material can be, but is not limited to, 2nm, 5nm, 8nm, 10nm, 13nm, 15nm, 18nm, 20nm, 23nm, 25nm, 27nm, 30nm, 33nm, 35nm, 38nm, 40nm, 43nm, 45nm, 47nm, 50nm or a range between any two of the above values. Optionally, the pore size of the porous conductive material is 15nm-35nm.
[0122] It should be noted that when the porous conductive material has only a single hole, the pore size of the hole refers to the pore size of the single hole; when the porous conductive material has multiple holes, the pore size of the hole refers to the average pore size of the holes.
[0123] As an example, the pore diameters of the above-mentioned pores can be measured by referring to the gas adsorption BET method in GB / T 19587-2017 using a specific surface area analysis tester.
[0124] In some embodiments, the stacking height of the first silicon-based material in the hole is 1nm-35nm; when the stacking height of the first silicon-based material in the hole is within the above range, the silicon-carbon material has a higher gram capacity, and its electrochemical performance is relatively stable and the cycle life is better; when the stacking height of the first silicon-based material in the hole is further increased, the conductivity of the silicon-carbon material particles drops sharply, thereby causing capacity decay. As an example, the stacking height of the first silicon-based material in the hole can be but is not limited to 1nm, 3nm, 5nm, 8nm, 10nm, 13nm, 15nm, 17nm, 20nm, 23nm, 25nm, 28nm, 30nm, 33nm, 35nm or a range between any two of the above values. Optionally, the stacking height of the first silicon-based material in the hole is 15nm-25nm.
[0125] It should be noted that the stacking height of the first silicon-based material in the hole refers to the stacking thickness of the first silicon-based material along the depth of the hole. When the first silicon-based materials all fall into the same hole, the stacking height of the first silicon-based material in the hole is the height of the first silicon-based material stacked in the hole. When the first silicon-based material falls into multiple holes, the stacking height of the first silicon-based material in the hole refers to the average stacking height of the first silicon-based material in the hole.
[0126] As an example, the stacking height of the first silicon-based material mentioned above in the pores can be measured using a transmission electron microscope (TEM).
[0127] As a possible implementation manner, the shape of the silicon-carbon material includes one or more of granular, spherical and quasi-spherical shapes.
[0128] In some embodiments, the first silicon-based material includes one or more of elemental silicon and a silicon-tin alloy.
[0129] In some embodiments, the shape of the first silicon-based material includes one or more of particles, wires, spheres, spheroids, and flakes.
[0130] In some embodiments, the porous conductive material comprises porous carbon.
[0131] In some embodiments, at least 3% of the first silicon-based material is embedded in the holes.
[0132] Optionally, all the first silicon-based materials are embedded in the holes; the volume expansion degree of the composite silicon material can be further reduced.
[0133] As a possible implementation, the composite silicon material also includes a first carbon coating layer, which is located between the substrate and the silicon-containing coating layer; the first carbon coating layer can act as a fast-charging ion ring, improve the kinetic properties of the composite silicon material, and reduce the contact between the silicon-carbon material and the electrolyte.
[0134] It should be noted that the “first carbon coating layer” in the present application is only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can it be understood as implicitly indicating the importance or quantity of the indicated technical features.
[0135] In some optional embodiments, the thickness of the first carbon coating layer is 10nm-30nm; when the thickness of the first carbon coating layer is within the above range, the silicon-carbon material has a higher gram capacity, and its electrochemical performance is relatively stable and the cycle life is better; when the thickness of the first carbon coating layer is further increased, the conductivity of the silicon-carbon material particles drops sharply, thereby causing capacity decay. As an example, the thickness of the first carbon coating layer can be, but is not limited to, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, 20nm, 21nm, 22nm, 23nm, 24nm, 25nm, 26nm, 27nm, 28nm, 29nm, 30nm or a range between any two of the above values.
[0136] As an example, the thickness of the first carbon coating layer mentioned above can be measured using a transmission electron microscope (TEM).
[0137] In some optional embodiments, the material of the first carbon coating layer includes amorphous carbon. Using amorphous carbon as the material of the first carbon coating layer has better ion conductivity and can also block direct contact between the silicon-based material and the electrolyte, thereby reducing side reactions.
[0138] In some embodiments, the composite silicon material further includes a second carbon coating layer, which is coated on the outside of the silicon-containing coating layer; the second carbon coating layer can act as a fast-charging ion ring, improve the kinetic properties of the composite silicon material, and reduce the contact between the silicon-containing coating layer and the electrolyte.
[0139] It should be noted that the “second carbon coating layer” in the present application is only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can it be understood as implicitly indicating the importance or quantity of the indicated technical features.
[0140] Optionally, the thickness of the second carbon coating layer is 10nm-30nm; when the thickness of the second carbon coating layer is within the above range, the second carbon coating layer has good ionic conductivity and high mechanical strength, and can tolerate the expansion of the silicon material to a large extent without breaking, thereby reducing the occurrence of side reactions. As an example, the thickness of the second carbon coating layer can be, but is not limited to, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, 20nm, 21nm, 22nm, 23nm, 24nm, 25nm, 26nm, 27nm, 28nm, 29nm, 30nm, or a range between any two of the above values.
[0141] As an example, the thickness of the second carbon coating layer mentioned above can be measured using a transmission electron microscope (TEM).
[0142] Optionally, the material of the second carbon coating layer includes amorphous carbon. When amorphous carbon is used as the material of the second carbon coating layer, the second carbon coating layer has better ion conductivity and can also block direct contact between the silicon-based material and the electrolyte, thereby reducing side reactions.
[0143] In some possible embodiments, the composite silicon material has a shape including one or more of a granular shape, a spherical shape, and a quasi-spherical shape.
[0144] In some optional embodiments, the volume average particle size Dv50 of the composite silicon material is 3μm-22μm; when the volume average particle size Dv50 of the composite silicon material is within the above range, it has a greater compaction density and a larger active specific surface. As an example, the volume average particle size Dv50 of the composite silicon material can be but is not limited to 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm or a range between any two of the above values. Optionally, the volume average particle size Dv50 of the composite silicon material is 5μm-10μm.
[0145] Dv50 refers to the particle size corresponding to the cumulative particle size distribution percentage of the sample volume reaching 50%. As an example, Dv50 can be conveniently measured by a laser particle size analyzer with reference to GB / T 19077-2016 particle size distribution laser diffraction method, such as the Mastersizer 2000E laser particle size analyzer of Malvern Instruments Ltd., UK.
[0146] In some embodiments, the composite silicon material comprises:
[0147] The inner core comprises a silicon-carbon material, the silicon-carbon material comprises a porous conductive material and a first silicon-based material, the outer surface of the porous conductive material has holes, and at least part of the first silicon-based material is embedded in the holes; the mass proportion of silicon element in the silicon-carbon material is 3%-25%, which can be 8%-10%; the pore size of the hole is 2nm-50nm, which can be 15nm-35nm; the stacking height of the first silicon-based material in the hole is 1nm-35nm, which can be 15nm-25nm; the shape of the silicon-carbon material includes one or more of granular, spherical and quasi-spherical; the first silicon-based material includes one or more of elemental silicon and silicon-tin alloy; the shape of the first silicon-based material includes one or more of granular, linear, spherical, quasi-spherical and flaky; the porous conductive material includes porous carbon; at least 3% of the first silicon granular silicon-based material is embedded in the hole;
[0148] A first carbon coating layer is coated on at least a portion of the outer surface of the substrate, the thickness of the first carbon coating layer is 10nm-30nm, and the material of the first carbon coating layer includes amorphous carbon;
[0149] A silicon-containing coating layer coated on at least part of the outer surface of the first carbon coating layer, the silicon-containing coating layer comprises an ion-conducting material and a second silicon-based material, and the second silicon-based material is dispersed in the ion-conducting material; the thickness of the silicon-containing coating layer is 5nm-100nm, and can be optionally 30nm-60nm; the volume average particle size Dv50 of the second silicon-based material is 2nm-20nm, and can be optionally 2nm-9nm; the second silicon-based material comprises one or more of elemental silicon and silicon-tin alloy; the shape of the second silicon-based material comprises one or more of particles, linear, spherical, quasi-spherical and flake; the ion-conducting material comprises one or more of hard carbon, soft carbon, graphite, transition metal nitride, silicon-based alloy, tin-based alloy and lithium metal; or the ion-conducting material and the second silicon-based material are composited into silicon oxide, and the molar ratio of oxygen element to silicon element contained in the silicon oxide is recorded as x, 0<x<2, and can be optionally 0<x≤0.6; and
[0150] A second carbon coating layer is coated on at least a portion of the outer surface of the silicon-containing coating layer, the thickness of the second carbon coating layer is 10nm-30nm, and the material of the second carbon coating layer includes amorphous carbon;
[0151] The shape of the composite silicon material includes one or more of granular, spherical and quasi-spherical shapes; the volume average particle size Dv50 of the composite silicon material is 3 μm-22 μm, and can be optionally 5 μm-10 μm.
[0152] The second aspect of the present application provides a method for preparing the composite silicon material of the first aspect, comprising the following steps: preparing a silicon-carbon material; and forming a silicon-containing coating layer on the outside of the silicon-carbon material.
[0153] The third aspect of the present application provides a method for preparing the composite silicon material of the first aspect, comprising the following steps: preparing a silicon-carbon material; forming a silicon dioxide coating layer on the outside of the silicon-carbon material to prepare an intermediate with a silicon dioxide coating layer; reducing the intermediate to form a silicon-containing coating layer on the outside of the silicon-carbon material.
[0154] In some embodiments, the silicon-carbon material is prepared by vapor deposition, which is beneficial to increase the proportion of the first silicon-based material embedded in the pores of the porous conductive material in the finally prepared silicon-carbon material, and even allows all the first silicon-based material to be deposited in the pores of the porous conductive material.
[0155] In some embodiments, the raw materials for preparing the silicon-carbon material include a porous conductive material and a first silicon source.
[0156] In some optional embodiments, the molar ratio of the porous conductive material and the first silicon source is (3-8):1; as an example, the molar ratio of the porous conductive material and the first silicon source can be but is not limited to 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1 or a range between any two of the above ratios.
[0157] In some alternative embodiments, the first silicon source includes monosilane.
[0158] In some alternative embodiments, the porous conductive material comprises porous carbon.
[0159] In some embodiments, the reaction temperature of the vapor deposition method is 800°C-900°C; for example, it can be but not limited to 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C or the range between any two of the above values. The reaction time is 2h-8h; for example, it can be but not limited to 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h or the range between any two of the above values.
[0160] In some embodiments, the reaction atmosphere of the vapor deposition method includes an inert gas; alternatively, the reaction atmosphere of the vapor deposition method includes argon gas.
[0161] In some embodiments, a silicon dioxide coating layer is formed on the outside of the silicon-carbon material by a hydrothermal method.
[0162] In some optional embodiments, the raw materials for preparing the silicon dioxide coating layer include a second silicon source.
[0163] Optionally, the second silicon source includes tetraethyl orthosilicate.
[0164] Optionally, the mass ratio of the silicon-carbon material to the second silicon source is 3:(1-5); for example, it can be but is not limited to 3:1, 3:1.5, 3:2, 3:2.5, 3:3, 3:3.5, 3:4, 3:4.5, 3:5 or a range between any two of the above ratios.
[0165] As a possible embodiment, the reaction temperature of the hydrothermal method is 110°C-130°C; for example, it can be but not limited to 110°C, 112°C, 115°C, 118°C, 120°C, 122°C, 125°C, 128°C, 130°C or the range between any two of the above values. The reaction time is 0.5h-5h; for example, it can be but not limited to 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h or the range between any two of the above values.
[0166] In some embodiments, the reaction medium of the hydrothermal method includes a mixture of ethanol and water.
[0167] Optionally, the volume ratio of ethanol to water in the mixed solution is (2-4): 1. As an example, the volume ratio of ethanol to water in the mixed solution can be, but is not limited to, 2: 1, 2.3: 1, 2.5: 1, 2.7: 1, 3: 1, 3.3: 1, 3.5: 1, 3.8: 1, 4: 1 or a range between any two of the above ratios.
[0168] In some embodiments, the intermediate is reduced using magnesium thermal reduction.
[0169] As a possible implementation, the reducing agent used includes magnesium powder.
[0170] Optionally, the mass ratio of the intermediate to the magnesium powder is (2-4):1; as an example, the mass ratio of the intermediate to the magnesium powder can be but is not limited to 2:1, 2.3:1, 2.5:1, 2.7:1, 3:1, 3.3:1, 3.5:1, 3.8:1, 4:1 or a range between any two of the above ratios.
[0171] As a possible implementation, the reaction temperature of the magnesium thermal reduction method is 600°C-750°C; for example, it can be but not limited to 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C or the range between any two of the above values. The reaction time is 0.5h-10h; for example, it can be but not limited to 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h or the range between any two of the above values.
[0172] In some embodiments, before the step of forming a silicon dioxide coating layer on the outer side of the silicon-carbon material, the step further includes: using a first carbon source to prepare a first carbon coating layer on the outer side of the silicon-carbon material.
[0173] Optionally, the first carbon source comprises acetylene.
[0174] In some optional embodiments, a first dilution gas is further added when preparing the first carbon coating layer, and the first dilution gas includes an inert gas.
[0175] Optionally, the first dilution gas includes argon.
[0176] Optionally, the volume ratio of the first carbon source to the first dilution gas is (0.5-2):9; for example, it can be but is not limited to 0.5:9, 0.8:9, 1:9, 1.3:9, 1.5:9, 1.7:9, 2:9 or a range between any two of the above values.
[0177] In some embodiments, the reaction temperature for preparing the first carbon coating layer is 600°C-800°C; for example, it can be but not limited to 600°C, 620°C, 650°C, 680°C, 700°C, 730°C, 750°C, 770°C, 800°C or the range between any two of the above values. The reaction time is 0.5h-2h; for example, it can be but not limited to 0.5h, 0.7h, 1h, 1.3h, 1.5h, 1.8h, 2h or the range between any two of the above values.
[0178] In some embodiments, a hydrothermal method is used to form a silicon dioxide coating layer on the outside of the first carbon coating layer.
[0179] In some optional embodiments, the raw materials for preparing the silicon dioxide coating layer include a second silicon source.
[0180] Optionally, the second silicon source includes tetraethyl orthosilicate.
[0181] Optionally, the mass ratio of the silicon-carbon material coated with the first carbon coating layer and the second silicon source is 3:(1-5); for example, it can be but is not limited to 3:1, 3:1.5, 3:2, 3:2.5, 3:3, 3:3.5, 3:4, 3:4.5, 3:5 or a range between any two of the above ratios.
[0182] As a possible embodiment, the reaction temperature of the hydrothermal method is 110°C-130°C; for example, it can be but not limited to 110°C, 112°C, 115°C, 118°C, 120°C, 122°C, 125°C, 128°C, 130°C or the range between any two of the above values. The reaction time is 0.5h-5h; for example, it can be but not limited to 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h or the range between any two of the above values.
[0183] In some embodiments, the reaction medium of the hydrothermal method includes a mixture of ethanol and water.
[0184] Optionally, the volume ratio of ethanol to water in the mixed solution is (2-4): 1. As an example, the volume ratio of ethanol to water in the mixed solution can be, but is not limited to, 2: 1, 2.3: 1, 2.5: 1, 2.7: 1, 3: 1, 3.3: 1, 3.5: 1, 3.8: 1, 4: 1 or a range between any two of the above ratios.
[0185] In some embodiments, the preparation method further comprises: using a second carbon source to form a second carbon coating layer on the outer side of the silicon-containing coating layer.
[0186] Optionally, the second carbon source comprises acetylene.
[0187] In some optional embodiments, a second dilution gas is further added when preparing the second carbon coating layer, and the second dilution gas includes an inert gas.
[0188] Optionally, the second dilution gas includes argon.
[0189] Optionally, the volume ratio of the second carbon source and the second dilution gas is (0.5-2):9; for example, it can be but is not limited to 0.5:9, 0.8:9, 1:9, 1.3:9, 1.5:9, 1.7:9, 2:9 or a range between any two of the above values.
[0190] In some embodiments, the reaction temperature for preparing the second carbon coating layer is 600°C-800°C; for example, it can be but not limited to 600°C, 620°C, 650°C, 680°C, 700°C, 730°C, 750°C, 770°C, 800°C or the range between any two of the above values. The reaction time is 0.5h-2h; for example, it can be but not limited to 0.5h, 0.7h, 1h, 1.3h, 1.5h, 1.8h, 2h or the range between any two of the above values.
[0191] It should be noted that the “first silicon source”, “second silicon source”, “first carbon source”, “second carbon source”, “first dilution gas” and “second dilution gas” in the present application are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features.
[0192] It should be noted that when the ion-conducting material and the second silicon-based material can be compounded into silicon oxide, before the step of preparing the second carbon coating layer, after the silicon-containing coating layer is coated, it can be mixed with a lithium supplement agent so that the silicon dioxide in the silicon-containing coating layer and the lithium supplement agent undergo an electrochemical reaction to form lithium silicate with ion conductivity.
[0193] In some embodiments, the method for preparing the composite silicon material comprises:
[0194] A silicon-carbon material is prepared by a vapor deposition method using a porous conductive material and a first silicon source as raw materials; the molar ratio of the porous conductive material to the first silicon source is (3-8):1, the first silicon source includes monosilane, the reaction temperature of the vapor deposition method is 800° C.-900° C., the reaction time is 2 h-8 h, and the reaction atmosphere of the vapor deposition method includes an inert gas;
[0195] A first carbon source is used to prepare a first carbon coating layer on the outer side of the silicon-carbon material; the first carbon source includes acetylene; a first dilution gas is also added during the preparation of the first carbon coating layer, the first dilution gas includes an inert gas; the first dilution gas includes argon, and the volume ratio of the first carbon source to the first dilution gas is (0.5-2):9; the reaction temperature is 600°C-800°C, and the reaction time is 0.5h-2h;
[0196] A silicon dioxide coating layer is formed on the outer side of a silicon-carbon material coated with a first carbon coating layer by a hydrothermal method to prepare an intermediate with a silicon dioxide coating layer; the raw material for preparing the silicon dioxide coating layer includes a second silicon source; the second silicon source includes tetraethyl orthosilicate; the mass ratio of the silicon-carbon material coated with the first carbon coating layer to the second silicon source is 3:(1-5); the reaction temperature of the hydrothermal method is 110° C.-130° C., and the reaction time is 0.5h-5h; the reaction medium of the hydrothermal method includes a mixed solution of ethanol and water, and the volume ratio of ethanol to water in the mixed solution is (2-4):1;
[0197] The intermediate is reduced by magnesium thermal reduction to form a silicon-containing coating layer on the outside of the first carbon coating layer; the reducing agent used includes magnesium powder, and the mass ratio of the intermediate to the magnesium powder is (2-4):1; the reaction temperature of the magnesium thermal reduction method is 600°C-750°C, and the reaction time is 0.5h-10h;
[0198] A second carbon source is used to form a second carbon coating layer on the outside of the silicon-containing coating layer; the second carbon source includes acetylene; a second dilution gas is also added when preparing the second carbon coating layer, and the second dilution gas includes an inert gas; the second dilution gas includes argon; the volume ratio of the second carbon source and the second dilution gas is (0.5-2):9; the reaction temperature is 600°C-800°C, and the reaction time is 0.5h-2h.
[0199] In some embodiments, the method for preparing the composite silicon material comprises:
[0200] The porous conductive material is placed in a rotary kiln, the rotation speed is adjusted to 1r / min-15r / min, and the first silicon source is injected at a flow rate of 0.1L / min-0.6L / min for 10min-40min. After the temperature is raised to 800℃-900℃, it is kept warm for 2h-8h to obtain a silicon-carbon material; after cooling, argon gas is passed into the rotary kiln for 30min, and the temperature is raised to 600℃-800℃ at 5℃ / min-15℃ / min, and the temperature is kept warm for 0.5h-2h; then the gas is switched to a mixed gas of the first carbon source and the first dilution gas with a volume ratio of (0.5-2):9, and the mixture is kept warm for 30min-120min. After cooling, C@Si-C is obtained;
[0201] The silicon-carbon material coated with the first carbon coating layer is dissolved in 100 ml of an ethanol aqueous solution with a volume ratio of (2-4):1, the second silicon source is added, and the mixture is stirred for 30 min, and then added into a 200 ml polytetrafluoroethylene-lined autoclave, heated to 110°C-130°C for 0.5h-5h, and then naturally cooled to room temperature; the obtained solution is centrifuged, repeatedly washed with anhydrous ethanol, and vacuum dried at 60°C for 12h to obtain SiO2@C@Si-C;
[0202] SiO2@first carbon coating layer@silicon-carbon material and Mg powder are mixed in a mass ratio of (2-4):1, fully ground and mixed in a mortar, heated in a 600℃-750℃ tube furnace in an inert gas atmosphere for 0.5h-10h, cooled to room temperature, washed with 0.5M hydrochloric acid to remove MgO and unreacted Mg, washed with deionized water to neutrality, and then vacuum dried at 70℃ for 12h; then placed in a rotary kiln, purged with argon for 30min, heated to 700℃ at 10℃ / min, and then switched to a mixed gas of a second carbon source and a second dilution gas in a volume ratio of (0.5-2):9, kept warm for 30min-120min, and cooled to obtain a C / SiOx@C / Si-C composite material.
[0203] It should be noted that C@Si-C means that a first carbon coating layer is coated on the outside of the silicon-carbon material; SiO2@C@Si-C means that a silicon dioxide coating layer is further coated on the outside of the first carbon coating layer; C / SiOx@C / Si-C means that a silicon-containing coating layer is formed outside the first carbon coating layer, and a second carbon coating layer is formed outside the silicon-containing coating layer.
[0204] The fourth aspect of the present application provides a negative electrode plate, comprising: a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, the negative electrode active material layer comprising the composite silicon material of the first aspect of the present application or the composite silicon material prepared by the method of the second aspect of the present application.
[0205] The negative electrode plate made of the composite silicon material mentioned above is used in the present application, and its plate rebound rate after full charge is significantly reduced, indicating that the volume expansion degree of the negative electrode plate is significantly reduced.
[0206] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0207] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material on a polymer material substrate. Among them, the metal material includes but is not limited to copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc., and the polymer material substrate includes but is not limited to polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE) and other substrates.
[0208] In some embodiments, the negative electrode active material can also simultaneously use negative electrode active materials for batteries that are well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material can be selected from at least one of elemental silicon, silicon-nitrogen complexes, and silicon alloys. The tin-based material can be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more. The weight ratio of the negative electrode active material in the negative electrode film layer is 70-100% by weight, based on the total weight of the negative electrode film layer.
[0209] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS). The weight ratio of the binder in the negative electrode film layer is 0-30% by weight, based on the total weight of the negative electrode film layer.
[0210] In some embodiments, the negative electrode film layer may further include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The weight ratio of the conductive agent in the negative electrode film layer is 0-20 weight %, based on the total weight of the negative electrode film layer.
[0211] In some embodiments, the negative electrode film layer may further include other additives, such as a thickener (such as sodium carboxymethyl cellulose (CMC-Na)), etc. The weight ratio of the other additives in the negative electrode film layer is 0-15% by weight, based on the total weight of the negative electrode film layer.
[0212] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry, wherein the solid content of the negative electrode slurry is 30-70wt%, and the viscosity at room temperature is adjusted to 2000-10000mPa·s; the obtained negative electrode slurry is coated on the surfaces of both sides of the negative electrode current collector, and after a drying process, cold pressing such as a roller is performed to obtain a negative electrode sheet. The unit surface density of the negative electrode powder coated on one side is 75-160g / 1540.25cm 2 , the compaction density of negative electrode is 1.2-2.0g / cm 3 .
[0213] The fifth aspect of the present application provides a secondary battery, comprising the negative electrode plate of the fourth aspect of the present application.
[0214] The secondary battery using the above-mentioned composite silicon material in the present application has improved fast charging capability and cycle performance.
[0215] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0216] Positive electrode
[0217] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.
[0218] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0219] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material on a polymer material substrate. Among them, the metal material includes but is not limited to aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc. The polymer material substrate includes but is not limited to one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0220] In some embodiments, the lithium ion positive electrode active material may include a positive electrode active material for a battery known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium phosphate containing an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxides (such as LiCoO 2 ), lithium nickel oxide (such as LiNiO 2 ), lithium manganese oxide (such as LiMnO 2 、LiMn 2 O 4 ), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (Also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O 2 (Also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O 2(Also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O 2 (Also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O 2 (Also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O 2 ) and its modified compounds, etc. Examples of lithium phosphates containing olivine structures may include, but are not limited to, lithium iron phosphate (such as LiFePO 4 (also referred to as LFP), composite materials of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO 4 ), at least one of a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. The weight ratio of the positive electrode active material in the positive electrode film layer is 80-100 weight%, based on the total weight of the positive electrode film layer.
[0221] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. The weight ratio of the binder in the positive electrode film layer is 0-20% by weight, based on the total weight of the positive electrode film layer.
[0222] In some embodiments, the positive electrode film layer may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The weight ratio of the conductive agent in the positive electrode film layer is 0-20% by weight, based on the total weight of the positive electrode film layer.
[0223] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry, wherein the positive electrode slurry has a solid content of 40-80wt%, and the viscosity at room temperature is adjusted to 5000-25000mPa·s, and the positive electrode slurry is coated on both sides of the positive electrode collector, and after drying, the positive electrode sheet is formed by cold rolling; the unit surface density of the positive electrode powder coated on one side is 180-400g / 1540.25cm 2 The compaction density of the positive electrode is 3.0-3.6g / cm 3 , optional: 3.3-3.5g / cm 3 The calculation formula of the compacted density is:
[0224] Compacted density = coating surface density / (thickness of the electrode after extrusion - thickness of the current collector).
[0225] Electrolytes
[0226] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0227] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0228] In some embodiments, the electrolyte salt may be selected from lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium perchlorate (LiClO 4 ) lithium hexafluoroarsenate (LiAsF 6 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO 2 F 2 ), lithium difluorobis(oxalate)phosphate (LiDFOP) and lithium tetrafluorooxalate)phosphate (LiTFOP). The concentration of the electrolyte salt is usually 0.5-5 mol / L.
[0229] In some embodiments, the solvent can be selected from one or more of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0230] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0231] Isolation film
[0232] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0233] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0234] In some embodiments, the isolation film has a thickness of 6-40 μm, and optionally 12-20 μm.
[0235] In some embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly by a winding process or a lamination process; and the electrode assembly and the electrolyte are packaged using the battery cell packaging material of the first aspect of the present application.
[0236] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 1 is a square structure as an example.
[0237] In some embodiments, reference Figure 2The outer package may include a shell 11 and a cover plate 13. The shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 can be covered on the opening to close the receiving cavity.
[0238] The positive electrode sheet, the negative electrode sheet and the separator can be wound or laminated to form an electrode assembly 12. The electrode assembly 12 is encapsulated in the housing cavity. The electrolyte is infiltrated in the electrode assembly 12. The number of electrode assemblies 12 contained in the lithium-ion battery 1 can be one or more, which can be adjusted according to demand.
[0239] In some embodiments, secondary batteries may be assembled into a battery module. The battery module may contain multiple secondary batteries, and the specific number may be adjusted according to the application and capacity of the battery module.
[0240] In the battery module, the plurality of secondary batteries may be arranged in sequence along the length direction of the battery module. Of course, they may also be arranged in any other manner. Further, the plurality of lithium-ion batteries may be fixed by fasteners.
[0241] Optionally, the battery module may further include a housing having an accommodation space, and the plurality of secondary batteries are accommodated in the accommodation space.
[0242] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0243] The battery pack may include a battery box and a plurality of battery modules disposed in the battery box. The battery box includes an upper box body and a lower box body, and the upper box body can be covered on the lower box body to form a closed space for accommodating the battery modules. The plurality of battery modules can be arranged in the battery box in any manner.
[0244] Electrical devices
[0245] In a sixth aspect, the present application provides an electrical device, which includes at least one of the secondary battery, battery module or battery pack on the fifth aspect of the present application. The secondary battery, battery module or battery pack can be used as a power source for the device, or as an energy storage unit for the device. The device may be, but is not limited to, a mobile device, an electric vehicle, an electric train, a ship and a satellite, an energy storage system, etc.; wherein the mobile device may include, but is not limited to, at least one of a mobile phone, a laptop computer, etc.; the electric vehicle may include, but is not limited to, at least one of a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.
[0246] The device can select a secondary battery, a battery module or a battery pack according to its usage requirements.
[0247] Figure 3 The power consumption device 2 is taken as an example. The power consumption device 2 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the high power and high energy density requirements of the device for the secondary battery, a battery pack or a battery module can be used.
[0248] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a lithium-ion battery may be used as a power source.
[0249] The beneficial effects of the present application are further illustrated below in conjunction with embodiments.
[0250] In order to make the technical problems, technical solutions and beneficial effects solved by the present application clearer, the following will be further described in detail with reference to the embodiments and drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work belong to the scope of protection of the present application.
[0251] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0252] 1. Preparation of composite silicon materials
[0253] Example 1
[0254] The porous carbon is placed in a rotary furnace, the rotation speed is adjusted to 6r / min, and in an argon atmosphere, 99.99% pure silane (as the first silicon source) is sprayed at a flow rate of 0.2L / min for 30 minutes, and the molar ratio of the porous carbon to the first silicon source is 4:1; after heating to 850°C, the temperature is kept for 4 hours for vapor deposition reaction to obtain a silicon-carbon material; after cooling, argon is introduced into the rotary furnace for 30 minutes, the temperature is raised to 700°C at 10°C / min, and then the gas is switched to a mixed gas of acetylene (as the first carbon source) and argon (as the first dilution gas) in a volume ratio of 1:9, and the temperature is kept for 30 minutes. After cooling, a first carbon coating layer is formed on the outside of the silicon-carbon material.
[0255] Weigh 3 g of the silicon-carbon material coated with the first carbon coating layer, dissolve it in 100 mL of a mixed solution of ethanol and water in a volume ratio of 2:1, add 2 g of tetraethyl orthosilicate (as a second silicon source), stir thoroughly for 30 minutes, and then add it to a 200 mL polytetrafluoroethylene-lined autoclave, heat it to 120°C and keep it warm for 1 hour, and then cool it naturally to room temperature; the obtained solution is centrifuged, and repeatedly washed with anhydrous ethanol, and vacuum dried at 60°C for 12 hours, that is, a silica coating layer is formed on the outside of the first carbon coating layer, and an intermediate with a silica coating layer is obtained.
[0256] The above intermediate was mixed with magnesium powder (as a reducing agent) in a mass ratio of 3:1, fully ground and mixed in a mortar, heated in a 650°C tubular furnace in an inert gas atmosphere for 2 hours for magnesium thermal reduction reaction, cooled to room temperature, washed with 0.5M hydrochloric acid to remove MgO and unreacted magnesium powder, washed with deionized water to neutrality, and then vacuum dried at 70°C for 12 hours to form a silicon-containing coating layer on the outside of the first coating layer; placed in a rotary kiln, purged with argon for 30 minutes, heated to 700°C at 10°C / min, and then switched to a mixed gas of acetylene (as a second carbon source) and argon (as a second dilution gas) in a volume ratio of 1:9, kept warm for 30 minutes, and formed a second carbon coating layer on the outside of the silicon-containing coating layer after cooling to obtain a composite silicon material.
[0257] The cross-sectional SEM image of the composite silicon material prepared in Example 1 is as follows: Figure 4 As shown. Figure 4 It can be seen that the composite silicon material has a coating structure, in which the silicon-containing coating layer is coated on the outside of the silicon-carbon material, the core material is a loading structure, the pores of the porous carbon contain elemental silicon (i.e., the first silicon-based material), and the coating layer is a dispersed structure, in which elemental silicon (i.e., the second silicon-based material) is dispersed in the silicon dioxide matrix.
[0258] Example 2-35
[0259] The preparation method of the composite silicon material in Examples 2-35 is basically similar to the preparation method of the composite silicon material in Example 1, and the main differences are: the type of the first silicon source, the molar ratio of porous carbon and the first silicon source, the temperature of the vapor deposition reaction, the time of the vapor deposition reaction, the type of the first carbon source, the type of the first dilution gas, the volume ratio of the first carbon source and the first dilution gas, the reaction temperature and / or time when preparing the first carbon coating layer, the type of the second silicon source, the mass ratio of the silicon-carbon material coated with the first carbon coating layer and the second silicon source, the reaction temperature and / or time when preparing the silicon dioxide coating layer, the type of the reducing agent for the magnesium thermal reduction reaction, the mass ratio of the intermediate with the silicon dioxide coating layer to the reducing agent, the temperature and / or time of the magnesium thermal reduction reaction, the type of the second carbon source, the type of the second dilution gas, the volume ratio of the second carbon source and the second dilution gas, and at least one of the reaction temperature and / or time when preparing the second carbon coating layer is different, see Table 1 for details.
[0260] Comparative Example 1
[0261] The difference between Comparative Example 1 and Example 4 is that only the silicon-carbon material and the first coating layer coated on the outside of the silicon-carbon material are prepared, as shown in Table 1-1 and Table 1-2 for details.
[0262] Table 1-1
[0263]
[0264] Table 1-2
[0265]
[0266] Among them, n1 represents the molar ratio of porous carbon to the first silicon source, n2 represents the mass ratio of the silicon-carbon material coated with the first carbon coating layer and the second silicon source, n3 represents the mass ratio of the intermediate with the silicon dioxide coating layer to the reducing agent, v1 represents the volume ratio of the first carbon source and the first dilution gas, and v2 represents the volume ratio of the second carbon source and the second dilution gas.
[0267] Comparative Example 2
[0268] The difference between Comparative Example 2 and Example 4 is that only the silicon-containing material and the second carbon coating layer coated on the outside of the silicon-containing material are prepared, and the silicon-carbon material and the first carbon coating layer coated on the outside of the silicon-carbon material are not included. The specific preparation process is as follows:
[0269] Pure SiO 2The mixture was mixed with Mg powder (mixing mass ratio of 3:1), ground and mixed thoroughly in a mortar, heated in an inert gas atmosphere at 650°C tube furnace for 2h, cooled to room temperature, washed with 0.5M hydrochloric acid to remove MgO and unreacted Mg, washed with deionized water to neutrality, and then vacuum dried at 70°C for 12h, placed in a rotary furnace, purged with argon for 30min, heated to 700°C at 10°C / min, and then switched to acetylene / Ar mixed gas (the volume ratio of acetylene to argon is 1:9), kept warm for 30min, and cooled to obtain a C / SiOx composite material with a carbon coating layer deposition thickness of 10nm.
[0270] Comparative Example 3
[0271] Step 1: Pure SiO 2 Mix with Mg powder (mixing mass ratio 3:1), grind and mix thoroughly in a mortar, heat in a 650℃ tube furnace in an inert gas atmosphere for 2h, cool to room temperature, wash with 0.5M hydrochloric acid to remove MgO and unreacted Mg, wash with deionized water to neutrality, and then vacuum dry at 70℃ for 12h, then put into a rotary furnace, pass argon gas to purge for 30min, heat to 700℃ at 10℃ / min, and then switch the gas to acetylene / Ar mixed gas (the volume ratio of acetylene to argon is 1:9), keep warm for 30min, and after cooling, a C / SiOx composite material with a silicon oxide layer deposition thickness of 10nm is obtained.
[0272] Step 2: Add 2 g of o-aminobenzenesulfonic acid and 2 g of lignin powder to the C / SiOx composite material obtained above, disperse in 150 mL of deionized water, mix thoroughly, transfer to a hydrothermal autoclave at 110°C to react for 8 h, centrifuge and wash the obtained solution, and dry in a vacuum drying oven at 60°C overnight.
[0273] Step 3: The solid powder obtained above was activated in a 50% by mass KOH solution for 12 h (impregnation ratio 1:3), then dried at 60°C, and then placed in a tubular furnace and kept at 700°C for 2 h under an argon atmosphere. After cooling, it was washed several times with 1.0 mol / L HCl to remove inorganic impurities, and then washed with deionized water until the filtrate was neutral. Finally, it was vacuum dried at 60°C for 12 h to obtain a C / Si-C@C / SiOx composite material.
[0274] The parameters of the composite silicon materials prepared in the above embodiments and comparative examples were measured, specifically including:
[0275] The mass proportion of silicon in the silicon-carbon material, the pore size of the porous carbon, the stacking height of the first silicon-based material in the pores, the thickness of the first coating layer, the thickness of the silicon-containing coating layer, the molar ratio of oxygen and silicon contained in the silicon oxide, the volume average particle size Dv50 of the second silicon-based material contained in the silicon oxide, the thickness of the second carbon coating layer and the volume average particle size Dv50 of the composite silicon material are specifically shown in Table 2.
[0276] Table 2
[0277]
[0278]
[0279] Among them, w1 represents the mass proportion of silicon element in silicon-carbon material, w2 represents the molar ratio of oxygen element to silicon element in silicon oxide, d1 represents the pore size of porous carbon pores, d2 represents the stacking height of the first silicon-based material in the pores, d3 represents the volume average particle size Dv50 of the second silicon-based material contained in silicon oxide, d4 represents the volume average particle size Dv50 of the composite silicon material, L1 represents the thickness of the first carbon coating layer, L2 represents the thickness of the silicon-containing coating layer, and L3 represents the thickness of the second carbon coating layer.
[0280] It should be noted that the mass percentage of silicon element in the above-mentioned silicon-carbon material is measured by EDS energy spectrum.
[0281] The pore size of the porous carbon pores mentioned above is measured by a specific surface area analysis tester with reference to the gas adsorption BET method in GB / T 19587-2017.
[0282] The stacking height of the first silicon-based material mentioned above in the pores is measured using a transmission electron microscope (TEM).
[0283] The thickness of the first carbon coating layer mentioned above is measured using a transmission electron microscope (TEM).
[0284] The molar ratio of oxygen and silicon in the silicon oxide mentioned above is determined by the following method: X-ray energy spectrum analysis is performed on the composite silicon material, the silicon content in the silicon-carbon material is deducted, and the X value in the silicon oxide is qualitatively determined.
[0285] The volume average particle size Dv50 of the second silicon-based material contained in the silicon oxide mentioned above is measured with reference to the particle size distribution laser diffraction method of GB / T19077-2016, using a Mastersizer 2000E laser particle size analyzer from Malvern Instruments Ltd., UK.
[0286] The thickness of the silicon-containing coating layer mentioned above is measured using a transmission electron microscope (TEM).
[0287] The thickness of the second carbon coating layer mentioned above is measured using a transmission electron microscope (TEM).
[0288] The volume average particle size Dv50 of the composite silicon material mentioned above is measured with reference to the particle size distribution laser diffraction method of GB / T 19077-2016, using a Mastersizer 2000E laser particle size analyzer from Malvern Instruments Ltd., UK.
[0289] It should be noted that since the volume average particle size Dv50 of the composite silicon material is at the micron level, the thickness of the first carbon coating layer, the thickness of the silicon-containing coating layer, and the thickness of the second carbon coating layer are only at the nanometer level. Therefore, the fluctuations in the thickness of the first carbon coating layer, the thickness of the silicon-containing coating layer, and the thickness of the second carbon coating layer have very little effect on the volume average particle size Dv50 of the composite silicon material and can be ignored.
[0290] 2. Preparation of negative electrode sheet and secondary battery
[0291] 1. Preparation of negative electrode sheet
[0292] The silicon-based materials prepared in the above embodiments and comparative examples were mixed with conductive carbon, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in a mass ratio of 10:85:1:1, and water was added. After stirring, the negative electrode slurry was prepared; the negative electrode slurry was evenly coated on both sides of a copper foil with a thickness of 6 μm, and the single-side coating surface density was 130 mg / 1540.25 mm 2 , dried in an oven, cold pressed and then die-cut with a slitting width of 43.5 mm to make a negative electrode sheet for a lithium-ion battery.
[0293] 2. Preparation of positive electrode
[0294] The positive electrode active material ternary material nickel cobalt manganese (NCM811), conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) were added to N-methylpyrrolidone (NMP) at a mass ratio of 97:2:1, and stirred evenly to prepare a positive electrode slurry; the positive electrode slurry was evenly coated on an aluminum foil with a thickness of 15 μm, and the surface density was 320 mg / 1540.25 mm 2 After drying, cold pressing is performed, and then die-cutting is performed, and the strip width is 40mm to make the positive electrode sheet of lithium-ion battery.
[0295] 3. Preparation of Isolation Membrane
[0296] Polyethylene is used as a base film, and aluminum oxide with a thickness of 3 μm is coated on the base film to obtain an isolation film.
[0297] 4. Preparation of Electrolyte
[0298] Ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1, and then LiPF 6 is uniformly dissolved in the above solution to obtain an electrolyte. In the electrolyte, LiPF 6 The concentration is 1 mol / L.
[0299] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play a role of isolation, and then the lithium-ion battery is obtained through packaging, liquid injection, formation and other processes.
[0300] It should be noted that the formation process in the preparation process of the above lithium-ion battery is: first charge to 3.0V at 0.02C, then charge to 3.4V at 0.1C, and finally charge to 3.9V at 0.2C.
[0301] 3. Negative electrode and secondary battery performance test
[0302] 1. Pole rebound rate test
[0303] After the secondary battery is fully charged, it is disassembled and the rebound rate of the negative electrode plate is tested. The rebound rate of the negative electrode plate = (thickness of the fully charged electrode plate / thickness of the cold pressed electrode plate-1)*100%. The results are shown in Table 3.
[0304] Full charge process: let the battery stand for 30 minutes, then charge at a rate of 0.5C to a voltage of 4.25V, further charge at a constant voltage of 4.25V to a current of 0.05C, and let it stand for 5 minutes.
[0305] 2. Fast charging capability test
[0306] The negative electrode sheets and the single-sided positive electrode sheets prepared in the above embodiments and comparative examples were respectively assembled into three-electrode small stacks, and their lithium precipitation windows were tested to calculate their fast charging capabilities (10-80% SOC);
[0307] Fast charging capability = 60*0.1 / (C 20% +C 30% +C 40% +C 50% +C 60% +C 70% +C 80% )
[0308] Among them, C xx% Indicates the maximum charge rate corresponding to the SOC; for example, C 20% It represents the maximum charge rate at 20% SOC. The results are shown in Table 3.
[0309] 3. Cycle capacity retention rate test
[0310] Test conditions: At room temperature, the battery is charged at a rate of 0.5C and discharged at a rate of 0.5C, and 300 full charge and discharge cycles are performed.
[0311] Test process: let the battery stand for 30 minutes, then charge at 0.5C rate to 4.25V, then charge at 4.25V constant voltage to 0.05C, let stand for 5 minutes, then discharge at 0.5C rate to 2.5V, this is a charge and discharge cycle. Record the discharge capacity at each cycle.
[0312] Capacity retention rate after 300 cycles (%) = (discharge capacity at the 300th cycle / discharge capacity at the first cycle) × 100%.
[0313] The results are shown in Table 3.
[0314] Table 3
[0315]
[0316]
[0317] From the comparison of the results of Examples 1-35 and Comparative Examples 1-3 in Table 3, it can be seen that in the present application, by using a silicon-carbon material and a silicon-containing coating layer comprising an ion-conducting material and a second silicon-based material in combination, and coating the silicon-containing coating layer on the outside of the silicon-carbon material to form a composite silicon material, the volume expansion of the negative electrode plate can be reduced, and the fast charging performance and cycle performance of the secondary battery can be improved.
[0318] The difference between Examples 1-7 is that the thickness of the silicon-containing coating layer is different. The thickness of the silicon-containing coating layer in Example 1 is the smallest, and the thickness of the silicon-containing coating layer in Example 7 is the largest. Compared with Examples 2-6, the fast charging time in Example 1 is extended. The technicians analyzed that the reason may be that: when the thickness of the silicon-containing coating layer is too low, the ion transmission path may increase limitedly, and the kinetic performance of the composite silicon material may be correspondingly poor. Compared with Examples 2-6, the rebound rate of the negative electrode plate in Example 7 is significantly increased, and the cycle capacity retention rate is significantly reduced. The technicians analyzed that the reason may be that: when the thickness of the silicon-containing coating layer is too high, the overall silicon content of the loaded silicon material is too high, which may cause the composite silicon material to expand too much, and further may cause the SEI film on the surface of the composite silicon material to be damaged, and the electrolyte consumes active lithium to continuously repair the SEI film at the damaged interface, thereby deteriorating the cycle performance.
[0319] The difference between Example 4 and Examples 8-13 mainly lies in the mass percentage of silicon in the silicon-carbon material and the stacking height of the first silicon-based material in the pores. The mass percentage of silicon in the silicon-carbon material and the stacking height of the first silicon-based material in the pores of Example 8 are the smallest, and the mass percentage of silicon in the silicon-carbon material and the stacking height of the first silicon-based material in the pores of Example 13 are the largest. Compared with Examples 4 and Examples 9-12, the fast charging time in Example 13 is longer and the cycle capacity retention rate is significantly reduced. The technicians analyzed that the reason may be that: the mass percentage of silicon in the silicon-carbon material is too large, which may cause the conductivity of the silicon-carbon material particles to drop sharply, and then This results in a decrease in fast charging performance and capacity attenuation, and a decrease in cycle performance; compared with Example 4 and Examples 9-12, the cycle capacity retention rate in Example 8 is significantly reduced. The technicians analyzed that the reason may be due to: when the mass proportion of silicon element in the silicon-carbon material is too small, the internal space of the silicon-carbon material particles may be larger after lithium insertion, and the mechanical strength of the silicon-carbon material particles is low. The composite silicon material may be easily broken under long-term high expansion during circulation, resulting in contact between the electrolyte and the internal silicon, increased side reactions, and a decrease in the cycle capacity retention rate; it should be noted that since the mass proportion of silicon element in the silicon-carbon material of Example 8 is relatively small, the gram capacity and energy density of the composite silicon material finally prepared are reduced.
[0320] The main difference between Example 4 and Examples 14-18 lies in the different molar ratios of oxygen and silicon in silicon oxide. From the results of Examples 4 and 14-18, it can be seen that when the molar ratio x of oxygen and silicon in silicon oxide is 0.6, the specific capacity of silicon oxide is relatively high and the volume expansion of silicon oxide during the cycle is small, there are fewer side reactions, the cycle performance is excellent, and more ion channels can be provided. Therefore, when x is 0.6, the composite silicon material can take into account both volume expansion and cycle performance and fast charging performance.
[0321] The main difference between Example 4 and Examples 19-22 is that the volume average particle size Dv50 of the second silicon-based material contained in the silicon oxide is different. The volume average particle size Dv50 of the second silicon-based material in Example 22 is the largest; from the results of Examples 4 and Examples 19-23, it can be seen that when the volume average particle size Dv50 of the second silicon-based material contained in the silicon oxide is 2-20nm, the active specific surface area of the second silicon-based material is large and the kinetic performance is better; at the same time, due to the small particle size of the second silicon-based material, the strain caused by different lithium concentrations is smaller, and the silicon oxide can withstand greater strain without breaking, and there are fewer side reactions, so that the composite silicon material has better fast charging capability and cycle performance, and excellent kinetic performance.
[0322] The difference between Example 4 and Examples 23-28 mainly lies in the different volume average particle size Dv50 of the composite silicon material. The volume average particle size Dv50 of the composite silicon material in Example 23 is the smallest, and the volume average particle size Dv50 of the composite silicon material in Example 28 is the largest; compared with Example 4 and Examples 24-27, the cycle capacity retention rate in Example 23 is reduced, and the fast charging time in Example 28 is extended; from the comparison of the above results, it can be seen that when the volume average particle size Dv50 of the composite silicon material is in the range of 3μm-22μm, the composite silicon material has a large active specific surface area and good kinetic properties; at the same time, due to its small particle size, it can withstand greater strain without breaking, and has fewer side reactions, and thus the composite silicon material has excellent cycle performance and fast charging performance.
[0323] The main difference between Example 4 and Examples 33-35 is that the settings of the first carbon coating layer and / or the second carbon coating layer are different; from the comparison of the results of Example 4 and Examples 33-35, it can be seen that by setting the first carbon coating layer and / or the second carbon coating layer, the cycle performance and fast charging performance of the composite silicon material can be improved.
[0324] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0325] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.
Claims
1. A composite silicon material, characterized in that: include: A core, the core comprising a silicon-carbon material, the silicon-carbon material comprising a porous conductive material and a first silicon-based material, the porous conductive material having holes on its outer surface, at least a portion of the first silicon-based material being distributed in the holes; and The silicon-containing coating layer is coated on the outer side of the inner core, and the silicon-containing coating layer comprises an ion-conducting material and a second silicon-based material, wherein the second silicon-based material is dispersed in the ion-conducting material.
2. The composite silicon material according to claim 1, characterized in that: The silicon-containing coating layer has at least one of the following characteristics: (1) The thickness of the silicon-containing coating layer is 5 nm-100 nm, and can be optionally 30 nm-60 nm; (2) The ion-conducting material includes one or more of hard carbon, soft carbon, graphite, transition metal nitride, silicon-based alloy, tin-based alloy and lithium metal; (3) The ion-conducting material and the second silicon-based material are composited into silicon oxide; Optionally, the molar ratio of oxygen element to silicon element contained in the silicon oxide is denoted as x, 0<x<2, and may be 0<x≤0.6; (4) The volume average particle size Dv50 of the second silicon-based material is 2nm-20nm, and can be 2nm-9nm; (5) The second silicon-based material includes one or more of elemental silicon and silicon-tin alloy; (6) The shape of the second silicon-based material includes one or more of particles, lines, spheres, quasi-spheres and flakes.
3. The composite silicon material according to any one of claims 1 to 2, characterized in that: The silicon-carbon material has at least one of the following characteristics: (1) The mass proportion of silicon in the silicon-carbon material is 3%-25%, and can be 8%-10%; (2) The pore diameter is 2nm-50nm, and can be 15nm-35nm; (3) The stacking height of the first silicon-based material in the hole is 1 nm-35 nm, and can be 15 nm-25 nm; (4) The shape of the silicon-carbon material includes one or more of granular, spherical and quasi-spherical shapes; (5) The first silicon-based material includes one or more of elemental silicon and silicon-tin alloy; (6) The shape of the first silicon-based material includes one or more of particles, lines, spheres, quasi-spheres and flakes; (7) The porous conductive material includes porous carbon.
4. The composite silicon material according to any one of claims 1 to 3, characterized in that: At least 3% of the first silicon-based material is embedded in the pores; Optionally, all of the first silicon-based materials are embedded in the holes.
5. The composite silicon material according to any one of claims 1 to 4, characterized in that: The composite silicon material further includes a first carbon coating layer, wherein the first carbon coating layer is located between the core and the silicon-containing coating layer; Optionally, the first carbon coating layer has at least one of the following characteristics: (1) The thickness of the first carbon coating layer is 10 nm to 30 nm; (2) The material of the first carbon coating layer includes amorphous carbon.
6. The composite silicon material according to any one of claims 1 to 5, characterized in that: The composite silicon material further includes a second carbon coating layer, wherein the second carbon coating layer is coated on the outer side of the silicon-containing coating layer; Optionally, the second carbon coating layer has at least one of the following characteristics: (1) The thickness of the second carbon coating layer is 10 nm to 30 nm; (2) The material of the second carbon coating layer includes amorphous carbon.
7. The composite silicon material according to any one of claims 1 to 6, characterized in that: The shape of the composite silicon material includes one or more of granular, spherical and quasi-spherical shapes; Optionally, the volume average particle size Dv50 of the composite silicon material is 3 μm-22 μm, and optionally 5 μm-10 μm.
8. A method for preparing a composite silicon material according to any one of claims 1 to 7, characterized in that: The steps include: preparing the silicon-carbon material; The silicon-containing coating layer is formed on the outer side of the silicon-carbon material.
9. A method for preparing a composite silicon material according to any one of claims 1 to 7, characterized in that: The steps include: preparing the silicon-carbon material; Forming a silicon dioxide coating layer on the outer side of the silicon-carbon material to prepare an intermediate with a silicon dioxide coating layer; The intermediate is reduced to form the silicon-containing coating layer on the outer side of the silicon-carbon material.
10. The method for preparing the composite silicon material according to claim 9, characterized in that: The silicon-carbon material is prepared by a vapor deposition method; Optionally, the vapor deposition method includes at least one of the following conditions: (1) The raw materials for preparing the silicon-carbon material include a porous conductive material and a first silicon source; Optionally, the molar ratio of the porous conductive material to the first silicon source is (3-8):1; Optionally, the first silicon source includes monosilane; Optionally, the porous conductive material comprises porous carbon; (2) The reaction temperature of the vapor deposition method is 800°C-900°C, and the reaction time is 2h-8h; (3) The reaction atmosphere of the vapor deposition method includes an inert gas.
11. The method for preparing a composite silicon material according to any one of claims 9 to 10, characterized in that: Forming a silicon dioxide coating layer on the outer side of the silicon-carbon material by a hydrothermal method; Optionally, the hydrothermal method includes at least one of the following conditions: (1) The raw materials for preparing the silicon dioxide coating layer include a second silicon source; Optionally, the second silicon source includes tetraethyl orthosilicate; Optionally, the mass ratio of the silicon-carbon material to the second silicon source is 3:(1-5); (2) The reaction temperature of the hydrothermal method is 110°C-130°C, and the reaction time is 0.5h-5h; (3) The reaction medium of the hydrothermal method comprises a mixture of ethanol and water; Optionally, the volume ratio of ethanol to water in the mixed solution is (2-4):
1.
12. The method for preparing a composite silicon material according to any one of claims 9 to 11, characterized in that: Reducing the intermediate by magnesium thermal reduction method; Optionally, the magnesium thermal reduction method includes at least one of the following conditions: (1) The reducing agent used includes magnesium powder; Optionally, the mass ratio of the intermediate to the magnesium powder is (2-4):1; (2) The reaction temperature of the magnesium thermal reduction method is 600°C-750°C, and the reaction time is 0.5h-10h.
13. The method for preparing a composite silicon material according to any one of claims 9 to 12, characterized in that: Before the step of forming a silicon dioxide coating layer on the outer side of the silicon-carbon material, the method further comprises: Using a first carbon source to prepare a first carbon coating layer on the outer side of the silicon-carbon material; Optionally, preparing the first carbon coating layer includes at least one of the following conditions: (1) The first carbon source includes acetylene; (2) adding a first dilution gas when preparing the first carbon coating layer, wherein the first dilution gas includes an inert gas; Optionally, the first dilution gas includes argon; Optionally, the volume ratio of the first carbon source to the first dilution gas is (0.5-2):9; (3) The reaction temperature is 600°C-800°C, and the reaction time is 0.5h-2h.
14. The method for preparing a composite silicon material according to any one of claims 9 to 13, characterized in that: The preparation method further comprises: Using a second carbon source to form a second carbon coating layer on the outer side of the silicon-containing coating layer; Optionally, preparing the second carbon coating layer includes at least one of the following conditions: (1) The second carbon source includes acetylene; (2) adding a second dilution gas when preparing the second carbon coating layer, wherein the second dilution gas includes an inert gas; Optionally, the second dilution gas includes argon; Optionally, the volume ratio of the second carbon source to the second dilution gas is (0.5-2):9; (3) The reaction temperature is 600°C-800°C, and the reaction time is 0.5h-2h.
15. A negative electrode plate, characterized in that: include: Anode current collector; as well as A negative electrode active material layer is located on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises the composite silicon material according to any one of claims 1 to 7 or the composite silicon material prepared by the method according to any one of claims 8 to 14.
16. A secondary battery, characterized in that: Comprising the negative electrode sheet as described in claim 15.
17. An electrical device, characterized in that: Comprising the secondary battery as claimed in claim 16.
Citation Information
Patent Citations
Core-shell structure micron silicon-carbon composite material and preparation method thereof, electrode and battery
CN115188939A
Silicon-carbon negative electrode material and application thereof
CN116454255A
Negative electrode material for nonaqueous electrolyte secondary battery, and preparation method therefor
WO2022021933A1
Cited By
Composite silicon material and preparation method therefor, negative electrode sheet, secondary battery, and electric device
EP4654293A1